2018
DOI: 10.1103/physreve.97.062314
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between synapses in pairs of neurons slow down dynamics in randomly connected neural networks

Abstract: Networks of randomly connected neurons are among the most popular models in theoretical neuroscience. The connectivity between neurons in the cortex is however not fully random, the simplest and most prominent deviation from randomness found in experimental data being the overrepresentation of bidirectional connections among pyramidal cells. Using numerical and analytical methods, we investigate the effects of partially symmetric connectivity on the dynamics in networks of rate units. We consider the two dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 69 publications
0
91
0
Order By: Relevance
“…the fact that the left-and right-eigenvectors of the connectivity matrix are not identical (Trefethen et al, 1993). A number of recent studies in theoretical neuroscience have pointed out the interesting dynamical properties of networks with non-normal connectivity (White et al, 2004;Ganguli et al, 2008;Murphy and Miller, 2009;Goldman, 2009;Hennequin et al, 2012Hennequin et al, , 2014Ahmadian et al, 2015;Martí et al, 2018). Several of these works (Murphy and Miller, 2009;Hennequin et al, 2012Hennequin et al, , 2014Ahmadian et al, 2015) have examined the amplification of the norm of the activity vector, as we do here.…”
Section: Discussionmentioning
confidence: 92%
“…the fact that the left-and right-eigenvectors of the connectivity matrix are not identical (Trefethen et al, 1993). A number of recent studies in theoretical neuroscience have pointed out the interesting dynamical properties of networks with non-normal connectivity (White et al, 2004;Ganguli et al, 2008;Murphy and Miller, 2009;Goldman, 2009;Hennequin et al, 2012Hennequin et al, , 2014Ahmadian et al, 2015;Martí et al, 2018). Several of these works (Murphy and Miller, 2009;Hennequin et al, 2012Hennequin et al, , 2014Ahmadian et al, 2015) have examined the amplification of the norm of the activity vector, as we do here.…”
Section: Discussionmentioning
confidence: 92%
“…Another possibility is that non-random features of the connectivity, such as the over-representation of reciprocal connections [65,66] slow down the dynamics away from any bifurcation. A recent study [67] has indeed found such a slowing-down. Weak connectivity structure of low-rank type provides yet another mechanism for the emergence of long timescales.…”
Section: Discussionmentioning
confidence: 78%
“…Contemporarily, the pivotal role of overlaps is understood in the simplest case of the evolution of complex Ginibre matrix -either in Smoluchowski-Fokker-Planck formalism [7,8] or in Langevin formalism [9], following the pioneering paper [10,11]. The effects of the overlaps of the Ginibre matrix for the temporal autocorrelation function of randomly connected networks was addressed analytically in the latest paper [5], confirming the numerical simulations in the weakly coupled regime of synaptic models.…”
Section: Introductionmentioning
confidence: 69%
“…In particular, the work of Marti et. al [5] shows that increasing the symmetry of the connectivity leads to a systematic slowing-down of the dynamics and vice versa, decreasing the symmetry of the matrix leads to the speeding of the dynamics. This non-normality of the matrix not only forces matrices to have complex spectrum (which challenges several traditional tools of random matrix theory), but more importantly, its study sheds new light on the role of Bell-Steinberger [6] matrix of overlaps between the left and right eigenvectors of the connectivity matrix.…”
Section: Introductionmentioning
confidence: 99%